Extracurricular arts: an effort to strengthen the character of global diversity in elementary school - Setiorini Rahma Safitri; Yunia Tiara Riski (Jurnal Ilmiah Pendidikan Dasar)
This study aims to explain an effort to strengthen the character of global diversity at SDN 1 Pringsurat, Temanggung Regency through extracurricular arts activities. The Merdeka Curriculum directs students to become people with character known as the 6 profiles of Pancasila students. One of the dimensions that is expected to be the character of Pancasila students today is global diversity, namely Indonesian students who have global competence but have personalities following Pancasila values. This study uses a qualitative method with a Phenomenological approach. The stages of the research were carried out in the form of data collection activities, data verification, data analysis-synthesis, and presentation in written form. The findings obtained in this study were that the extracurricular arts implemented at SDN 1 Pringsurat in the form of training and performances of Soreng Dance, regional songs, Islamic songs, and national songs were real practices of efforts to strengthen the character of global diversity. The presence of various art materials shows the diversity of values such as local, spiritual, and national values which are manifested in the "arts festival" of multicultural education. The goal is that humans as part of a global society that follows world progress trends, are not uprooted from the roots of their nation's culture. The result is that the nation's noble values, such as love of the homeland, patriotism, and diversity are instilled in students from an early age.